“Bello sexo” in the Galician Press in the Revolutionary Six-Year Period - Arcay Barral, Ángel (Madrygal. Revista de Estudios Gallegos, 2015)
This article discusses the presence of women writers in Galician press during the period from 1856 to 1880, based on a small percentage of Galician newspapers from that time in order to explore women’s participation in press publications. First of all, I will try to relate 19th century legislation to the amount of published newspapers. Furthermore, I will connect the presence of women in education with their participation in press publications from that period.